2013
DOI: 10.1007/s00264-013-2184-y
|View full text |Cite
|
Sign up to set email alerts
|

Bergapten prevents lipopolysaccharide mediated osteoclast formation, bone resorption and osteoclast survival

Abstract: Purpose This study was designed to investigate the potential effect of bergapten on lipopolysaccharide (LPS)-mediated osteoclast formation, bone resorption and osteoclast survival in vitro. Methods After osteoclast precursor RAW264.7 cells were treated with bergapten (5, 20, 40 μmol/L) for 72 hours in the presence of LPS (100 ng/ml), osteoclastogenesis was identified by tartrate-resistant acid phosphatase (TRAP) staining, and the number of TRAP-positive multinucleated cells [TRAP(+ )MNCs] per well were counted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Bergapten (BP; C 12 H 8 O 4 ), a natural anti-inflammatory and anti-tumor agent isolated from bergamot essential oil, other citrus essential oils and grapefruit juice, has been used to prevent lipopolysaccharide (LPS)-mediated osteoclast formation, bone resorption and osteoclast survival in vitro (19). Bergapten has also been shown to significantly inhibit the production of pro-inflammatory cytokines (20).…”
Section: Introductionmentioning
confidence: 99%
“…Bergapten (BP; C 12 H 8 O 4 ), a natural anti-inflammatory and anti-tumor agent isolated from bergamot essential oil, other citrus essential oils and grapefruit juice, has been used to prevent lipopolysaccharide (LPS)-mediated osteoclast formation, bone resorption and osteoclast survival in vitro (19). Bergapten has also been shown to significantly inhibit the production of pro-inflammatory cytokines (20).…”
Section: Introductionmentioning
confidence: 99%
“…BP is a natural coumarin found in many plants such as grasses, orchids, citrus fruits, and legumes. The effect of BP on bacteria-induced inflammatory bone loss has already been reported [15]. Moreover, it can enhance bone formation by osteoblasts in vitro and in vivo [16,32], suggesting that BP has the potential to prevent or treat osteoporosis by promoting the osteogenic differentiation of BMSCs.…”
Section: Discussionmentioning
confidence: 96%
“…1a), a coumarin found in many medicinal plants, has been used for decades in combination with UV radiation in skin photochemotherapy [8]. It also has many other biological functions, including anti-cancer [9][10][11], anti-oxidative [12,13], anti-inflammatory [14], and anti-resorptive effects [15]. Recently, researchers reported that BP stimulates the activity of rat primary osteoblasts and enhances bone morphogenetic protein-2 expression and bone formation via the p38 and extracellular signal regulated kinase-dependent pathway [16].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, BG has been proven to suppress inflammation by inhibiting the recruitment of neutrophils and macrophages in a tail-cutting-induced zebrafish injury site and reducing reactive oxygen species and nitric oxide generation [15]. Furthermore, Zheng et al [16] found that BG inhibited osteoclastogenesis and bone resorption stimulated by LPS, which suggests BG could be taken as a possible treatment of inflammatory bone-destructive diseases. Thus, BG may be a potential candidate for OA therapy.…”
mentioning
confidence: 99%